2021
DOI: 10.1186/s12884-021-03773-x
|View full text |Cite|
|
Sign up to set email alerts
|

Health providers’ and pregnant women’s perspectives about smoking cessation support: a COM-B analysis of a global systematic review of qualitative studies

Abstract: Background Smoking cessation in pregnancy has unique challenges. Health providers (HP) may need support to successfully implement smoking cessation care (SCC) for pregnant women (PW). We aimed to synthesize qualitative data about views of HPs and PW on SCC during pregnancy using COM-B (Capability, Opportunity, Motivation, Behaviour) framework. Methods A systematic search of online databases (MEDLINE, EMBASE, PsycINFO and CINAHL) using PRISMA guidel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 71 publications
(258 reference statements)
0
13
0
Order By: Relevance
“…In the UK, specialised midwives and a ‘stop smoking in pregnancy service’ with the exclusive aim of working with women to improve smoking cessation rates in pregnancy have been introduced [ 57 ]. As the previous paragraph indicates, health providers already experience time restrictions, overwhelming workloads and work in systems that are not conducive for supporting implementation and monitoring of smoking cessation in pregnancy [ 39 , 51 , 61 ]. Women in SA will continue to be disengaged from smoking cessation if they do not have a supportive health service that utilises contemporary, evidence-based approaches and health providers that have time and capacity to implement them.…”
Section: Discussionmentioning
confidence: 99%
“…In the UK, specialised midwives and a ‘stop smoking in pregnancy service’ with the exclusive aim of working with women to improve smoking cessation rates in pregnancy have been introduced [ 57 ]. As the previous paragraph indicates, health providers already experience time restrictions, overwhelming workloads and work in systems that are not conducive for supporting implementation and monitoring of smoking cessation in pregnancy [ 39 , 51 , 61 ]. Women in SA will continue to be disengaged from smoking cessation if they do not have a supportive health service that utilises contemporary, evidence-based approaches and health providers that have time and capacity to implement them.…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review of pregnant women's views about smoking cessation support received from health professionals, similarly analyzed using the COM‐B model, pregnant women's physical capability to quit (e.g. increased metabolism of nicotine and dependence) was seldom addressed because of uncertainty about NRT use in pregnancy 27,28 . Improving women's motivation to quit depended on health professionals explaining the risks of smoking versus the safety of quitting smoking methods.…”
Section: Discussionmentioning
confidence: 99%
“…increased metabolism of nicotine and dependence) was seldom addressed because of uncertainty about NRT use in pregnancy. 27,28 Improving women's motivation to quit depended on health professionals explaining the risks of smoking versus the safety of quitting smoking methods. Pregnant women considered advice from health professionals during antenatal visits to be effective, if accompanied by resources, peer support, feedback, and encouragement.…”
Section: Coffs Harbour -2mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the risks of smoking during pregnancy are well documented, presentation of the benefits of not smoking may be more beneficial in encouraging pregnant women to stop smoking. A recent review of attitudes towards smoking cessation programs found that healthcare workers found it difficult to communicate health advice on smoking during pregnancy without making the pregnant woman feel guilty and damaging the relationship with the pregnant woman [ 26 ]. The same study reported pregnant women feeling pressured and stigmatized for smoking.…”
Section: Discussionmentioning
confidence: 99%